Evaluate the efficacy of "heat stress audits" of your cooling system through core body temperature - John F. Smith; M. VanBaale; C. Jamison; R. Rodriguez (Kansas Agricultural Experiment Station Research Reports, 2006)
A project to evaluate the degree of heat stress in individual dairies was carried out in the summer of 2005. The object of this project was to develop a method to evaluate or audit how effective an individual dairy is in manag-ing heat stress. Approximately 45 herds in 20 different states were audited for the degree of heat stress cows experienced during a 72-hr period. Dairies were selected based on geog-raphy, climate, and facility design. Lactating cows 40 to 100 days in milk (DIM) and dry cows within 30 days of calving were evalu-ated. Vaginal temperatures of 8 cows located in the same group were collected every 5 min by using data loggers (HOBO U12®) attached to a vaginally placed insert (blank CIDR®). Ambient climatic data were collected on the project dairies by using logging devices that collected temperature and relative humidity at 5-min intervals. Census data were collected at each dairy, and included pen sizes, milking frequency, milking times, average milk pro-duction, DIM, parity, holding-pen design, and timing of cow movements. Data were im-ported into Excel (Microsoft, Redmond, WA) as individual cow files aligned by time. The data for an individual cow were then averaged with all other cows in the pen in hourly incre-ments over a 24-hr period. Each hour of the 24-hr period is then a summary of that hour on 3 consecutive days, with 8 devices contribut-ing 12 points per hour per day to the sum-mary. So each hour is a summary of 12 data points x 8 cows x 3 days, or 288 data points per hour. Information was summarized graphically in PowerPoint (Microsoft, Red-mond, WA) and presented to the individual producers, along with recommendations on how to improve their heat-stress abatement practices. The project was not designed as a controlled experiment; therefore, caution is advised in over-interpreting the results. That being said, the project does demonstrate the feasibility and usefulness of using intra-vaginal temperature recording to monitor how well an; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Body temperature; Cooling; Heat stress